‘In Response to Online Customer Compliments’: The Effects of Webcare Towards Positive eWOM on Observing Consumers’ Pre-purchase Decision- making - Chutrakul, Varin (2020)
The digital era has empowered consumers with the ability to voice their positive and negative customer experiences online, expressed as electronic word-of-mouth (eWOM). This has granted consumers significant control over what brand- and firm- related information becomes communicated to others, thereby shifting power relations between firms and consumers. To counteract this, webcare (i.e. firm responses to eWOM) has surfaced as a tool to wrestle online communications back under control. Recently, firms have expanded their scope from using webcare to placate or defend against customer complaints (negative eWOM), to using webcare to address and thank customer compliments (positive eWOM). As a public phenomenon, firm responses to customer compliments are not only witnessed by message recipients but also observing consumers searching for information prior to making purchase decisions. This study thus investigated the effects of webcare addressed at positive eWOM on observing consumers’ pre-purchase decision-making. Specifically conceptualising webcare as a service encounter, the study proposes that providing webcare to positive eWOM can affirm expectations about the dedication of service employees and therefore positively reinforce observing consumers’ trust, especially if responses are personalised. By means of an experiment, findings demonstrate webcare addressed at positive eWOM can engender not only positive but negative effects on trust (cognitive and affective) depending on the degree of message personalisation. The mediating role of personalisation had a larger magnitude of effect on trust than expected. While personal webcare produced high levels of trust as intended, impersonal webcare produced extremely low levels of trust which was even lower than when webcare was absent. 2 Overall, this study provides additional support for the beneficial, as well as initial support for the detrimental effects of webcare when addressed at positive eWOM. These effects possess implications on purchase intentions, as well as broader customer experience. On a practical level, findings contribute to clarifying the business value of providing firm responses to customer compliments. For marketers who monitor, manage, or aim to leverage eWOM communications, providing firms responses to customer compliments can help to foster trust that is helpful for solving a number of different business challenges. However, in order to elicit these effects, marketers must not only respond but respond in a specific way. Marketers need to ensure that webcare responses are personalised to each individual customer. If lacking the resources and capabilities to do so, this study supports that webcare to positive eWOM should not be provided at all.